Disambiguation Of The Nunatak Viedma: A Basement Block Previously Confused As A Volcanic Center - Blampied, Javier (2012)
Historically, the nunatak Viedma was confused with a volcano because its air-view morphology resemble that of a volcanic center, and there was a lack of proper fieldwork. Our field-data shows mainly sedimentary sequences, affected by metamorphism that can be classified as schist and gneiss affected majorly by isoclinal folding. We conclude that the nunatak Viedma is not from volcanic origin due to the observation of exclusively metamorphic outcrops, and its morphology shaped by conspicuous glacial landforms.